1985
DOI: 10.1002/cbf.290030212
|View full text |Cite
|
Sign up to set email alerts
|

Utility and sensitivity of anti BrdU antibodies in assessing S‐phase cells compared to autoradiography

Abstract: A rapid and convenient method for estimating S-phase cells in a population was developed which detects bromodeoxyuridine (BrdU) incorporation into DNA by means of monoclonal anti-BrdU antibodies. This immunofluorescence technique (RPMB technique) was compared to autoradiographic (ARG) detection of tritiated thymidine (3HTdr) grains incorporated into the DNA. Using incubation periods for BrdU and 3HTdr ranging from one minute to one hour and detecting their incorporation by ARG and RPMB techniques, it became ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…gain or loss of chromosomes) from manual handling. It is unlikely that any cells had progressed into early S-phase, as even short BrdU/EdU incorporation periods (1 min) are clearly detectable [53], For ELISA, it was necessary to perform high-throughput mitotic shake-off, slightly increasing contamination with S-phase cells compared to manual selection. S-phase cells contain fewer fully methylated histones [54,55], reducing histone methylation in nuclear G 1 cell extracts.…”
Section: Discussionmentioning
confidence: 99%
“…gain or loss of chromosomes) from manual handling. It is unlikely that any cells had progressed into early S-phase, as even short BrdU/EdU incorporation periods (1 min) are clearly detectable [53], For ELISA, it was necessary to perform high-throughput mitotic shake-off, slightly increasing contamination with S-phase cells compared to manual selection. S-phase cells contain fewer fully methylated histones [54,55], reducing histone methylation in nuclear G 1 cell extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Like [3H]-thymidine, BrdU can be used in vivo [16][17][18][19] and in vitro [20]. The sensitivity [14,[21][22][23] and specificity [22] of BrdU immunodetection for labeling S-phase cells are comparable to [3H]-thymidine autoradiography.…”
Section: Introductionmentioning
confidence: 88%
“…Raza et al reported that the BrdU LI and the tritiated thymidine LI were almost the same 7 . Using enzymatic treatment and acid hydrolysis, BrdU-incorporated cells were detected even in formalin-fixed samples 8 .…”
Section: Discussionmentioning
confidence: 93%